Meningkatkan Hasil Belajar Materi Mengenal Nama Allah dan Kitab-Nya melalui Model Pembelajaran Kooperatif Tipe Inside Outside Circle pada Mata Pelajaran Pendidikan Agama Islam - Fathonah, Siti (Paedagogie, 2021)
This study aims to determine the increase in student learning outcomes in Islamic Religious Education learning the subject matter of Knowing the Name of Allah and His Book at SD N Grinting 02, Bulakamba District, Brebes Regency by using a cooperative learning strategy type inside outside circle in class V A. This study is a Classroom Action Research (CAR). The research model used is the cycle model developed by Kemmis and Taggart. The subjects in this study were class V A students of SD Negeri Grinting 02 Bulukamba District, Brebes Regency with a total of 32 students, consisting of 16 male students and 16 female students for the 2019/2020 academic year. This classroom action research was carried out in 2 (two) cycles, each cycle consisting of planning, action, observation, evaluation and reflection stages. Each cycle is carried out in 2 meetings. The indicator of success in this study is an increase in student learning outcomes seen from the increase in the class average which reaches 84 and the percentage of complete learning reaches 91%. Based on the results of observations, students can establish positive communication between students in the learning process and increase student learning outcomes in Islamic Religious Education lessons. Learning outcomes increased from pre-cycle, cycle 1 and cycle 2 (61,73,84, the same thing also happened in the percentage of completeness (28%, 59%, 91%). that has been determined by researchers and observers, the application of the inside outside circle type of cooperative learning strategy can improve the learning outcomes of Islamic Religious Education for class VA students at SD Negeri Grinting 02, Bulakamba District, Brebes Regency for the 2019/2020 academic year.